Assessment of Pharmacokinetic and Pharmacodynamic Interactions Between Albumin-Fused Mutated Butyrylcholinesterase and Intravenously Administered Cocaine in Recreational Cocaine Users. Issue 4 (August 2015) - Shram, Megan J.; Cohen-Barak, Orit; Chakraborty, Bijan; Bassan, Merav; Schoedel, Kerri A.; Hallak, Hussein; Eyal, Eli; Weiss, Sivan; Gilgun, Yossi; Sellers, Edward M.; Faulknor, Janice; Spiegelstein, Ofer
Introduction Cocaine dependence presents a major public health issue, and to date, no pharmacotherapies are approved for its treatment. TV-1380 is a novel recombinant albumin-fused mutated butyrylcholinesterase (Albu-BChE) that has increased catalytic efficiency for cocaine compared with wild-type BChE and therefore has the potential to facilitate abstinence in cocaine-dependent subjects by decreasing exposure to cocaine and its reinforcing effects. Methods This randomized, double-blind, placebo-controlled, parallel-group study in nondependent cocaine users was conducted to evaluate the effect of a single intramuscular dose of Albu-BChE (50, 100, and 300 mg) on the pharmacokinetic and metabolic profile of intravenous cocaine infusions (40 mg) administered at baseline and at 24, 96, and 168 hours after Albu-BChE dosing, to assess safety of coadministering Albu-BChE and cocaine, and to explore the subjective responses to cocaine infusions after Albu-BChE dosing. Results Administration of Albu-BChE resulted in significant dose-dependent reductions in cocaine exposure (maximum concentration, area under the curve) and half-life. Effects were greatest at 24 hours after Albu-BChE dose, but were sustained up to 168 hours. Spearman correlations indicated a significant negative relationship between Albu-BChE concentration and cocaine clearance and exposure. Consistent with its mechanism of action, Albu-BChE also shifted cocaine metabolism toward preferential formation of ecgonine methyl ester. Administration of Albu-BChE was associated with modest decreases in subjective reports of feeling high and willingness to take cocaine again after cocaine infusion. Coadministration of Albu-BChE and cocaine was safe and well tolerated. Conclusions Administration of Albu-BChE at single doses of 50, 100, and 300 mg safely resulted in long-lasting decreases in cocaine exposure in recreational cocaine users.